AS DIRETRIZES CURRICULARES PARA A EDUCAÇÃO PROFISSIONAL DO ESTADO DO PARANÁ À LUZ DOS PRINCÍPIOS GRAMSCIANOS: A IMPLEMENTAÇÃO ANALISADA SOB A PERSPECTIVA DOCENTE - Estacheski, Joice (2013)
documental survey and field study, its general objective is the critical analysis of the Professional Education State Curricular Guidelines in Paraná (2006) (DCEs in the Brazilian abbreviation), in order to better understand its role in the current social organization, once it uses Marxist contributions regarding polytechnics and Gramsci‟s proposal of unitary school, which uses work as an educational principle, it proposes to educate the working class in an emancipating way. Thus, through the dialecticalhistorical materialism, this study tries to elucidate the conditions in which the professional education was built in the modern society, characterizing the immediate bourgeois interest in the expropriation of workers. Based on authors such as Alves (2001), Cunha (1999; 2005), Saviani (2008), and Marx (1999; 2011) the study outlines the history of professional education as an educational policy, in different economical contexts, from the law at Federal and State levels, as well as the emergency established to resume this kind of education in the Paraná State, even before the Decree 2.208/97 had been repealed. Through this Marxist conceptual approach proposed in the document, under which the conceptions of work and education are discussed as well as their correlation with SEED-PR objectives, the study also explores the categories of polytechnical education, unitary school and work as an educational principle, supported by Marx‟s (2011) and Gramsci‟s conceptions and the discussions proposed by Saviani (2007), Nosella (2007) Soares (2000), highlighting the documents conceptual gaps, once the DCEs do not approach certain categories which, for Gramsci (2001), (2004) were significant for his theoretical constructions on education, such as the concept of enlarged State,historical block, civil society and passive revolution. Through the field research and analysis of data obtained through questionnaires, the subjects involved in the research were characterized, people who work as teachers in the professional education, in the municipality of Ponta Grossa, Paraná, and had their conception problematized, as intellectuals who are responsible for the concretization of the Paraná Professional Education State Curricular Guidelines, and whom, according to the SEED/PR, are organic to the working class. Therefore, the study is also an attempt to reach the understanding and comprehension of these teachers towards the DCEs and its philosophical theoretical foundations, trying to situate them in the context of professional education, as well as the working conditions they are currently given. Being the DCEs a proposal theoretically concerned with the working classes,the findings of this study are not motivating in the perspective of the subalterns,revealing a conciliation-based proposal serving the capital, disguised under a democratic discourse, once the professional education, conceived according to the DCEs, brings in its origins a huge theoretical and conceptual mistake, as for the working class offspring the education remains partial, fragmented and promotes the division between manual and intellectual work. These features reveal the appropriation of concepts different from those which were in its origins and its real political intentions. Taking these reflections into consideration, we intend to contribute with the discussions of public policies for Basic Education in high school, in order to emphasize the need to overcome the political-ideological discourse within the professional education.